O papel do gênero na experiência do desemprego de casais portugueses e brasileiros - Aguiar, Joyce Cristina dos Santos (2017)
Among the most notorious consequences of the current international financial crisis is the high unemployment rate, in both Brazil and Portugal. Studies indicate that, during periods of economic recession, there is an increase in psychosocial problems, as uncertainty about finding another job causes a decrease in individual well-being. Most studies on the effects of unemployment have been focused on the psychological impacts at the individual level. Few studies have examined how unemployment affects the family, by using different configurations of family unemployment (male unemployment, female unemployment and families in which both members of the couple are unemployed) or by investigating crossover effects, to understand how the condition of the unemployed individual affects other family members. In this study, a first qualitative analysis revealed not only negative aspects but also positive aspects of being unemployed, underscoring the importance of protective factors in this context. Given that families are complex systems, in which individuals participate simultaneously in at least three subsystems (individual, marital and parental), this research aimed to analyze the role of individual and family variables on each subsystem’ satisfaction (satisfaction with life, marital satisfaction and parental satisfaction). Given that professional and family involvements is different according to gender, three family configurations related to unemployment were examined (male unemployment, female unemployment and both couple members unemployment). In both the Portuguese and the Brazilian samples, the group in which both partners were unemployed was the most vulnerable group, with lower ratings of satisfaction. Marital empathy, self-efficacy and family cohesion were relevant predictors of parental, marital and life satisfaction. The protective effect of these variables differed according to the family configuration of unemployment and by gender, but not by country. Crossover effects between members of the couple were observed in families in which women were unemployed: the more empathic the men are, the greater the marital satisfaction of the wives. For the female unemployed group, both spouses’ perception of family cohesion affected their own satisfaction with life, as well as their spouse’s. The results highlight the intensity of unemployment over the family, regardless of the country, evidencing a universal component of the unemployment experience.